THE INFLUENCE OF COMPANY VALUE AND COMPANY SIZE ON FINANCIAL PERFORMANCE IN THE FINANCIAL SECTOR DURING 2022 - Putri, Mega Amalia; Royani, Asri; Surya Saputra, Muhamad Ikbal; Tarwisah, Iyang Siti (IJMA (Indonesian Journal of Management and Accounting), 2024)
Financial performance is an assessment of a company's performance to see whether a company is good or not by calculating financial ratios. This research aims to determine the influence of company value and size on financial performance in the financial sector during 2022. The data used is secondary data in the form of financial reports of companies listed on the IDX. The sample used was 40 financial reports in the financial sector. The sample in this study used non-probability sampling with a total of 45 data tested with SMART PLS 4.0. The data analysis technique in this research uses the Structural Equation Modeling (SEM) technique. This research shows that in the financial sector in 2022, company value has no effect on financial performance. On the other hand, company size influences financial performance.